Sodium-Glucose Co-Transporter Type 2 Inhibitors and Heart Failure: A Review of the State of the Art - Yilmar Alexader Meza-González; Natalia Alfonso-Arrieta; Stephany Salas-Solorzano; Victor Florez-Garcia (Iberoamerican Journal of Medicine, 2023)
Heart Failure (HF) is a cardiovascular condition with high morbidity and mortality that conditions one of the most critical problems in public health. Despite advances in recent decades, patients continue to have major cardiovascular events and marked reduction in their quality of life. Sodium-Glucose Cotransporter Type 2 Inhibitors (SGLT2 Inhibitors) initially entered the market to treat hyperglycemia in patients with type 2 diabetes mellitus (T2DM), however the discovery of the cardiovascular benefits in patients with HF, regardless of the presence or absence of T2DM positioned it as a new pillar in clinical management. In this state-of-the-art review resulting from a comprehensive literature search (Medline, Cochrane and EMBASE), we describe the impact of SGLT2 Inhibitors on mortality and rehospitalizations in patients with HF and we propose a therapeutic plan for patients with HF to maximizes the benefits.